Didactic-pedagogical proposals for environmental education using school gardens (Research, Society and Development, 2020)
Environmental education is an essential component that must be present in the curriculum at all levels of school education. Its importance is given by promoting a critical environmental and food awareness, forming individuals capable of intervening in their reality, seeking improvements in the quality of life. Based on experiences with extension projects carried out at the Federal Institute of Education, Science and Technology of Minas Gerais, Campus Bambuí, it was realized the need to carry out works that presented proposals for activities in the gardens associated with the formal requirements of the guiding documents of the education. In order to reconcile and consequently meet the contents defined in the Environment area contained in the National Curriculum Plans, this work sought to list the contents related to the themes contained in the document and correlate them with didactic-pedagogical activities to be worked on in the School Garden Environment. Activities that are essential in the process of implementing and maintaining a school garden have been described, from planning to harvest. In the description of each activity, a correlation was made with the contents provided for in the National Curriculum Plans - Environment, seeking to list the activities and contents that are proposed to be addressed in the school garden practices. After assessing the correlations, it can be concluded that most of the contents related to the Environment proposed in the document can be worked on in the activities to be carried out. In addition, it was possible to certify that work in the school garden environment can be used as content in addressing different points that are foreseen in the curriculum.